Knock-down of USP22 by small interfering RNA interference inhibits HepG2 cell proliferation and induces cell cycle arrest - Ling, S. B.; Sun, D. G.; Tang, B.; Guo, C.; Zhang, Y.; Liang, R.; Wang, L. M. (Cellular and Molecular Biology, 2012)
The Ubiquitin-specific protease 22 (USP22) is a new putative cancer stem cell marker, which plays a significant role in tumorigenesis and cell-cycle progression. However, little is known about the impact of USP22 knock-down on the growth of human hepatoma cell lines. In this study, elevated expression of USP22 was observed in the human HepG2 hepatic cancer cell line compared to the normal human hepatocyte Chang liver cell line. Subsequently, we used siRNA specifically suppressing expression of USP22 and observed that the knock-down of USP22 could effectively induce cell cycle arrest and inhibit HepG2 cell proliferation. Furthermore, our results showed that USP22 deletion caused down-regulation of cyclin D2 expression and up-regulation of p15 and p21 expression. Collectively, Our findings indicate that USP22 may be responsible for HepG2 cell growth and USP22 regulates the cell cycle via the c-Myc/cyclin D2 pathway and down-regulating p15 and p21 expression in HepG2 cell.